2021
DOI: 10.1093/cid/ciab643
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Incidence of Asymptomatic SARS-CoV-2 Among Early Recipients of COVID-19 Vaccines (DISCOVER-COVID-19): A Prospective Cohort Study of Healthcare Workers Before, During and After Vaccination

Abstract: The impact of COVID19 vaccination on viral characteristics of breakthrough infections is unknown. In this prospective cohort study, incidence of SARS-CoV-2 infection decreased following vaccination. Although asymptomatic positive tests were observed following vaccination, higher cycle thresholds, repeat negative tests and inability to culture virus raises questions about their clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
2
20
0
4
Order By: Relevance
“…BNT162b2 administration coincided with a significant decrease in wastewater positivity for SARS-CoV-2 RNA concurrent with a decreasing incidence of COVID-19 as observed via clinical testing. This is consistent with observations from clinical samples that found that breakthrough infections of vaccinated individuals were associated with lower virus loads, faster clearance, and the absence of culturable virus . Because of the observational study design, the effects of secular trends on COVID-19 cases on campus, such as changes in campus activity due to reading days and final exams, changes in COVID-19 incidence among the community outside the university, and changes in behavior associated with weather, could not be assessed.…”
Section: Resultssupporting
confidence: 71%
“…BNT162b2 administration coincided with a significant decrease in wastewater positivity for SARS-CoV-2 RNA concurrent with a decreasing incidence of COVID-19 as observed via clinical testing. This is consistent with observations from clinical samples that found that breakthrough infections of vaccinated individuals were associated with lower virus loads, faster clearance, and the absence of culturable virus . Because of the observational study design, the effects of secular trends on COVID-19 cases on campus, such as changes in campus activity due to reading days and final exams, changes in COVID-19 incidence among the community outside the university, and changes in behavior associated with weather, could not be assessed.…”
Section: Resultssupporting
confidence: 71%
“…Viral load quantification and sequencing was conducted as previously reported ( 14 ). Briefly, we pelleted virions from nasal swab fluids after centrifugation at 21,000 g for 2 hours at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…We additionally performed spike gene amplification, as previously described ( 14 ), to determine variant types for specimens with low viral load to determine variants when whole-genome sequencing was unsuccessful. We used Superscript IV reverse transcriptase (Invitrogen) to conduct cDNA synthesis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As of June 15, 2021, 90% of individuals living in the greater Boston area had either previously been infected by SARS-CoV-2 and/or were vaccinated. While reinfection can occur despite prior infection and vaccine breakthrough infections occur, those 90% of individuals are much less likely to be at risk of severe COVID-19 were they to now acquire SARS-CoV-2 infection [7][8][9][10][11] . Among the remaining individuals who are therefore at higher risk for severe COVID-19 infection, Black and/or Hispanic individuals are disproportionately represented.…”
Section: Discussionmentioning
confidence: 99%